2015
DOI: 10.1186/s40635-015-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging reactive oxygen species using tempol in the acute phase of renal ischemia/reperfusion and its effects on kidney oxygenation and nitric oxide levels

Abstract: BackgroundRenal ischemia/reperfusion (I/R) injury is commonly seen in kidney transplantation and affects the allograft survival rates. We aimed to test our hypothesis that scavenging reactive oxygen species (ROS) with tempol would protect renal oxygenation and nitric oxide (NO) levels in the acute phase of renal I/R.MethodsRats were randomly divided: (1) no I/R, no tempol; (2) no I/R, but with tempol; (3) I/R without tempol; and (4) I/R with tempol. I/R was induced by 30-min clamping of the renal artery. Tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 33 publications
4
40
0
1
Order By: Relevance
“…Although not confirmed experimentally, this effect is likely related to the superoxide scavenging properties of TEMPOL, as a result of which hydrogen peroxide production and corollary NF-κB activation [79,80] and thus iNOS hyperactivation and NO overproduction are suppressed. Our parallel study with suprarenal artery clamping as a model for I/R AKI [58] demonstrated a considerable drop in renal NO levels at 90 min reperfusion (reflecting an increase in peroxynitrite formation). The intrarenal NO concentration was restored to pre-I/R levels by TEMPOL pretreatment in that model, implying that peroxynitrite formation was blocked due to reduced superoxide production.…”
Section: Tempol Reduces I/r-induced Renal Inos and Il-6 Expressionmentioning
confidence: 79%
See 4 more Smart Citations
“…Although not confirmed experimentally, this effect is likely related to the superoxide scavenging properties of TEMPOL, as a result of which hydrogen peroxide production and corollary NF-κB activation [79,80] and thus iNOS hyperactivation and NO overproduction are suppressed. Our parallel study with suprarenal artery clamping as a model for I/R AKI [58] demonstrated a considerable drop in renal NO levels at 90 min reperfusion (reflecting an increase in peroxynitrite formation). The intrarenal NO concentration was restored to pre-I/R levels by TEMPOL pretreatment in that model, implying that peroxynitrite formation was blocked due to reduced superoxide production.…”
Section: Tempol Reduces I/r-induced Renal Inos and Il-6 Expressionmentioning
confidence: 79%
“…To validate our I/R AKI model and the pharmacodynamic effects of TEMPOL in juxtaposition to the results obtained in literature and our parallel study with renal artery occlusion [58], the degree of iNOS expression, oxidative stress, kidney damage, and inflammation were analyzed first in rats subjected to 30 min of renal ischemia followed by 90 min of reperfusion. This I/R regimen has been standardly employed as a model for AKI [68,69].…”
Section: Characterization and Validation Of The Ischemia/reperfusion mentioning
confidence: 87%
See 3 more Smart Citations